Court of Pacifica - Roberts & Roberts:::::::::
Mexican folklore musicians next to sculpture "Inca Indian" by Sargent Johnson. Fountain of Western Waters at right center. Mural "The Peacemakers" by Helen Esther and Margaret Bruton in left background.